The Relationship Between Perceptions Of Disease And Long Suffering Self-Care Management Of Diabetes Mellitus Patients In Lamadukelleng Regional General Hospital Sengkang, Wajo District, South Sulawesi - Ramli, Rachmat (Sean Institute, 2022)
Self-care is self-care management to prevent complications in people with diabetes mellitus. Several factors influence a person's self-care, namely the Perception of the disease and the duration of suffering from diabetes mellitus. This study aimed to examine the relationship, direction, and closeness of the relationship between the Perception of the disease and the length of suffering in patients with type 2 diabetes mellitus. This type of research is a quantitative study with a correlational design and a cross-sectional approach. The sample of this study was 74 respondents who were taken using the purposive sampling technique. Data collection using the B-IPQ and SDSCA-Revised questionnaires. Data analysis using Spearman Rank test. The results showed that the average Perception of the disease was 48.59, the average length of suffering was 5.00 years, and the average self-care for diabetes mellitus patients was 48.58. There is a significant correlation between the Perception of the disease and the self-care of Diabetes mellitus patients, with a p-value = 0.00. There is no significant relationship between the length of suffering and self-care of people with diabetes mellitus, with a p-value = 0.132 (p > 0.05). It is recommended for people with diabetes mellitus to carry out self-care following what is recommended by PERKENI, especially in physical activities and foot care according to procedures. As well as health workers can provide information about diabetes mellitus to improve the patient's Perception of the disease.